Changes in rainfall amount and seasonality modulate taxonomic, functional, and phylogenetic diversity in a gypsophilous plant community in the Chihuahuan Desert. (5th December 2022) - Vargas-Colin, Alexa; Flores, Joel; Romo-Campos, Rosa; Douterlungne, David; Yáñez-Espinosa, Laura; González, José M.; Luzuriaga, Arantzazu L.
ABSTRACT: Background: Climate change is expected to alter future rainfall regime in arid zones, which may impact gypsophilous plant diversity components in the Chihuahuan Desert. Aims: We investigated the effects of different rainfall timings and amounts on the taxonomic, functional, and phylogenetic components of a gypsophilous plant community. Methods: We used soil monoliths extracted from the southern Chihuahuan Desert in a greenhouse experiment with three rainfall timings (typical, early, and late) and two rainfall amounts (100% and 50%) and evaluated the effects on taxonomic, functional, and phylogenetic diversity. Results: Irrigation treatment with 50% of average rainfall reduced species richness and plant abundance and altered species composition. At 100% irrigation, specific leaf area was lower in the treatments with typical and late rainfall timing than in the treatment with early rainfall. Phylogenetic diversity was significantly lower in the late timing treatment in November. Conclusion: Our study evidence that the water shortage impacted drastically on the plant community by decreased species richness and diversity. Nevertheless, late rainfall can buffer the effects of water diminution but only on taxonomic and functional diversity, with the opposite effect on the phylogenetic diversity, in the gypsophilous communities in the Chihuahuan Desert.